PEMBERDAYAAN REMAJA MILENIAL BERBASIS EKONOMI KREATIF MELALUI HOME INDUSTRY KERAJINAN BAMBU: - - Zul Jalal Hadi; Achban; Dian Endang Lestari; Didik Pratama; Huda Riskika; Iwon Susilowati; Muhammad Thoyyib Fuady; Muhammad Yunus; Nabilah Nisa’uzzakiyyah; Nurul Wisa Adiana; Edy Herianto (LP2M Universitas Hasanuddin, 2021)
The bamboo handicraft home industry is a breakthrough in creative economy development technology for millennial youth in Desa Suka Makmur, Kabupaten Lombok Barat. If this is developed, then the potential for bamboo that has been neglected can be processed and managed to provide added value that can drive the community's economy. This activity aims to empower millennial youth groups based on the creative economy through the development of a bamboo handicraft home industry. The stages and methods of activities used include socialization (discussion and FGD), team building (collaborative and cooperative), training (practical and assignments), and pilot demonstration (demonstration). The results of the activity were in the form of increased understanding of the target subject related to the concept of the importance of introducing bamboo with its potential value and efforts to develop handicrafts as a superior product of the community, namely 5% enough category, 80% good category, and 15% excellent category; the formation of the bamboo handicraft home industry as a place to create creations of various handicraft products from bamboo and the practice of marketing products through social media, websites, bazaar activities and exhibitions organized by local governments. — Home industry kerajinan bambu merupakan terobosan teknologi pengembangan ekonomi kreatif bagi para remaja milenial di Di Desa Suka Makmur Kabupaten Lombok Barat. Jika hal itu dikembangkan, maka potensi bambu yang selama ini terabaikan dapat diolah dan dikelola agar memberikan nilai tambah yang mampu menggerakkan perekonomian masyarakat. Tujuan kegiatan ini adalah untuk memberdayakan kelompok remaja milenial berbasis ekonomi kreatif melalui pengembangan home industry kerajinan bambu. Tahapan dan metode kegiatan yang digunakan antara lain: sosialisasi (metode diskusi dan FGD), pembentukan tim (metode kolaboratif dan kooperatif), pelatihan (metode praktik dan penugasan), dan demonstrasi percontohan (metode demonstrasi). Hasil dari kegiatan berupa meningkatnya pemahaman subyek sasaran terkait konsep pentingnya pengenalan bambu dengan potensi nilai yang dimilikinya dan upaya pengembangan kerajinan sebagai produk unggulan masyarakat yakni 5% kategori cukup, 80% kategori baik, dan 15% kategori baik sekaIi; terbentuknya home industry kerajinan bambu sebagai tempat untuk membuat kreasi berbagai produk kerajinan dari bambu dan praktik memasarkan produk melalui sosial media, website, kegiatan bazar dan pameran yang diselenggarakan oleh pihak pemerintah daerah.